Ovarian contrast-enhanced ultrasonography and Doppler fluxometry in bitches during the postovulatory estrus and corpora lutea formation - Nogueira Aires, Luiz Paulo [UNESP] (2022)
The aim of the present study was to evaluate the vascularization features of canine ovaries during the follicular phase and the formation of the corpora lutea by using Doppler ultrasonography and Contrast-Enhanced Ultrasound (CEUS). Eight healthy bitches were enrolled in the study and were evaluated at five different timepoints (T1 – T5) of the estrous cycle established by vaginal cytology and serum progesterone concentration. Ultrasonographic examinations were performed by a single operator using the ACUSON S2000/SIEMENS machine equipped with a linear multifrequency transducer (9.0 MHz). Color-coded Doppler evaluation of the ovarian parenchyma was performed to investigate the aspects of the signal detection throughout the different timepoints. Pulsed-wave Doppler of the intraovarian arteries was performed to evaluate spectral waveform and doppler velocimetric parameters of Systolic Peak Velocity (SPV cm/s), End Diastolic Velocity (EDV cm/s), Resistivity Index (RI) and Pulsatility Index (PI). CEUS evaluation of the ovaries was performed using a vascular contrast agent (SonoVue®, Bracco, Sao Paulo, Brazil) and the CADENCE™ Contrast Pulse Sequencing (CPS, Siemens) software, in order to perform both qualitative and quantitative analysis. Perfusion parameters of pixel number, peak intensity (PPI in %), time to peak intensity (TTP in s), mean transit time (MTT in s) and area under the curve (AUC in %). Colour-coded Doppler evaluation demonstrated an increase in signal detection as cycle progressed, with blood flow initially detected with few coloured pixels and mainly at the ventral surface of the ovaries. Further on, the number of coloured pixels increased and spreading to the central region, resulting in a circular-like pattern around the corpora hemorrhagica. The spectral waveform was consistent at all timepoints. SPV (cm/s) and EDV (cm/s) presented a numeric trend and a slight statistical difference at all timepoints, whereas no difference was found for RI and PI. CEUS evaluation demonstrated an increase in pixel intensity across all the timepoints. Quantitative CEUS analysis revealed a statistical difference in PPI (%), MTT (s) and AUC (%) at T5. CEUS evaluation of the ovaries was feasible and demonstrated a marked increase in perfusion parameters in the late postovulatory period, demonstrating its applicability in the assessment of canine corpora lutea development.